Case Report: Transient antenatal bartter syndrome in an extremely preterm infant with a novel MAGED2 variant - Yang, Hongyuan; Liu, Zhiyong; Wu, Yaying; Xu, Jinglin; He, Ying; Wang, Ruiquan; Zhang, Weifeng; Chen, Dongmei (Frontiers in Pediatrics, 2023)
Variants in the MAGED2 may cause antenatal transient Bartter syndrome, which is characterised by polyhydramnios, preterm labour, postnatal polyuria, hypokalaemia and metabolic alkalosis. Transient gross haematuria and acute kidney injury in such cases have not been reported previously. The patient, a boy, was born at a gestational age of 27 + 5 weeks. Polyhydramnios has been detected at 24 weeks of gestation. Polyuria, hyponatraemia, hypokalaemia, weight loss, transient haematuria and acute kidney injury occur after birth. The urinary ultrasonography showed no abnormality, and after a month of treatment with liquid electrolytes and nutritional management, the clinical symptoms improved. Whole-exome sequencing revealed a variant in MAGED2: c.1426C>T, p.Arg476X, inherited from the mother, who was healthy. During the 1-year follow-up, the child grew and developed with normal renal function and electrolyte levels. This is the first report of transient antenatal Bartter syndrome caused by a MAGED2 variant in China in an extremely preterm infant who exhibited previously unreported symptoms: transient haematuria and acute kidney injury. This newly found variant expands the spectrum of genetic variants associated with antenatal Bartter syndrome; it can be detected by early genetic testing and overmedication, thereby avoided.